A study on the reaction mechanism of microwave pyrolysis of oily sludge by products analysis and ReaxFF MD simulation. Issue 13 (7th June 2022) - Wen, Yanjun; Li, Wenxuan; Xie, Yingshen; Qin, Zhiwen; Gu, Meixia; Wang, Tianli; Hou, Yingfei
ABSTRACT: The products distributions of oily sludge (OS) pyrolysis was fully explored by combining the pyrolysis experiments and molecular simulation, to help to deeply understand this complicated reaction process. The results of products analysis indicated that the main reactions include chain-breaking reactions, dehydrogenation reactions, aromatization reactions, alkylation reactions, and dehydrogenation condensation reactions. Microwave pyrolysis of model OS comprised of n-dodecane and OS sediment were conducted to further explore the specific reaction during the pyrolysis process, and the results showed that the pyrolysis of saturated alkanes begins at 350℃, and dehydrogenation condensation begins at 500℃. Specifically, saturated alkanes first dehydrogenated to form large molecules of α-alkene, then α-alkenes broke chains to form smaller molecules of alkanes. Furthermore, the pyrolysis process of n-dodecane was simulated by Reactive force field molecular dynamics (ReaxFF MD), and the molecular pyrolysis products distribution obtained by simulation was in good agreement with the experimental result. GRAPHICAL ABSTRACT: UF0001